SUSTAINABLE CONCEPTS OF MACEDONIAN TRADITIONAL ARCHITECTURE FROM THE 19TH AND 20TH CENTURY - Temelkovski, Branko (Faculty of Design and Technology of furniture and interior – Skopje, 2021)
At a time when urban environments are growing rapidly at the expense of basic environmental and socio-cultural values, the topic of sustainable design is becoming increasingly relevant. Sustainable development over the past few decades has emerged as an integral part of most engineering disciplines. On the other hand, the knowledge acquired from the traditional architecture comprises complex and rich range of environmental values. The aim of this research is to detect principal aspects of environmental design in Macedonian traditional residential architecture from the 19th and 20th century, as well as to perceive the potential for implementation of its values and qualities in terms of space, identity, culture and environment in the contemporary context, rather in a technical than in a vernacular sense. The research was conveyed through separate analysis of the environmental, socio-cultural and socio-economic principles typical of that architecture, in a way to detect architectural concepts compatible with the modern approach of the architectural practice. Also it is necessary to find a way to stimulate new forms of vitalizing the neglected areas by developing modern sustainable concepts wherever applicable, in accordance with the current physical, socio-cultural and economic standards.
Keywords: Sustainable design, Architecture, Traditional architecture, Socio-cultural context